ChemInform Abstract: Metal‐Free Diimide Reduction of Alkenylphosphonates: Simple and Efficient Protocol for the Synthesis of α‐Substituted Ethylphosphonates. Issue 29 (June 2016) - Fang, Yewen; Yuan, Meijuan; Jin, Xiaoping; Zhang, Li; Li, Ruifeng; Yang, Shaoshuai; Fang, Mei
Abstract: An efficient and simple method for the synthesis of α‐substituted ethylphosphonates via diimide reduction of α‐substituted vinylphosphonates is reported.